Latin as the Language of Science and Learning - Roelli, Philipp (Lingua Academica, 2021)
This book approaches its topic from three angles: diachronic semantics, a panorama of science and scientific writing in Latin from antiquity up to the present, and linguistic forays that try to demarcate scientific Latin from other registers and to identify groups of different language use among the authors introduced in the panorama. The transition of science from Greek through Latin to the modern vernaculars is especially emphasised.